Model Model Desain Pembelajaran PAI (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Islamic Religious Education (PAI) faces the challenge of developing effective learning models in order to create relevant and quality learning experiences. This study aims to analyze various PAI learning design models that can be implemented in the classroom to improve learning effectiveness. The approach used in this study is descriptive qualitative with a literature study method, where data is collected from various written sources relevant to the topic. The analysis technique applied is content analysis, which aims to evaluate the characteristics, advantages, and disadvantages of each learning model. The results of the study indicate that classroom-oriented, product-oriented, and system-oriented learning design models each have advantages in certain contexts. The classroom-oriented model is effective in creating a conducive learning environment, the product-oriented model supports independent learning with structured teaching materials, and the system-oriented model integrates all learning components to achieve more holistic goals. In conclusion, the selection and implementation of the right learning design model according to the needs of students and the educational context can significantly improve the quality of PAI learning, as well as provide practical contributions to the development of learning methodology in schools.